2014
DOI: 10.1016/j.apcbee.2014.10.050
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Workers Productivity Under Simulated Environmental Factor by Taguchi Analysis

Abstract: The objective of this study is to determine the dominance impact of environmental factors such as illuminance, humidity and temperature on worker productivity by Taguchi Method. A study was conducted under simulated environment factor which examined were the illuminance, humidity and temperature of the surrounding workstation area in the closed simulation lab. A set of representative data including the illuminance, humidity and temperature level and production rate were collected during the study. The producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…High relative indoor humidity can limit the cooling system's performance, as was shown in our previous study [15]. High relative indoor humidity has also been found to be detrimental to thermal comfort and productivity [16]. While the active cooling technologies that currently dominate the market are well established and have comparatively lower upfront costs, they may come with long-term negative impacts on energy demand and greenhouse gas emissions [6].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…High relative indoor humidity can limit the cooling system's performance, as was shown in our previous study [15]. High relative indoor humidity has also been found to be detrimental to thermal comfort and productivity [16]. While the active cooling technologies that currently dominate the market are well established and have comparatively lower upfront costs, they may come with long-term negative impacts on energy demand and greenhouse gas emissions [6].…”
Section: Introductionmentioning
confidence: 72%
“…The ventilation demand for both modelled systems is calculated to be 0.6 l/(sm 2 floor area ) (0.53 ACH), according to category II of the EN 15251 standard for very low-polluting office buildings [35]. The modelled AHU operation schedule follows the occupancy of the building, starting one hour before the first occupant arrives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The studied dehumidification system is a condensing dehumidifier.…”
Section: Details Of the Studied Hvac Systemmentioning
confidence: 99%
“…Furthermore, the impact of climate or weather also significantly impacts construction project materials or labor resources. Ismail et al [63] and Zhang et al [64] concluded that it can be empirically proven that environmental factors such as temperature and relative humidity have a significant impact on workers' performance, whereas Amadi [65] claimed that the meteorological profile of wet-humid climates induces a significantly high percentage of the variance in the real-time demand for bagged cement on construction sites, which reveals that the issue should also be evaluated from a different perspective in terms of activity-specific material demand and supply. This should be one of the results of the duration and cost variability of construction activities during different periods.…”
Section: Discussionmentioning
confidence: 99%
“…n) is the j index value of the i order parameter. The efficiency coefficient U ij of each system to the whole can be expressed as formula (1).…”
Section: ) Construction Of Efficacy Functionmentioning
confidence: 99%
“…Ismail studied the effects of various factors on the work efficiency of operators by simulating different light, temperature and humidity conditions in a laboratory. Temperature was found to be the main factor affecting the work efficiency, followed by light and relative humidity [1]. Mook et al studied the relationship between the working efficiency and environmental parameters.…”
Section: Introductionmentioning
confidence: 99%